Implementation of Husband's Rights to Annul Marriage Due to False Identity in the Religious Courts of Metro Lampung City - Huzaini Husin; Arne Huzaimah; Jalaluddin Jalaluddin; Nor Ipansyah; Sardjana Orba Manullang; Vivit Fitriyanti (Faculty of Law, Universitas Pekalongan, 2023)
At this time, in the contemporary and modernization era, it is easier for couples who want to get married, especially with economic conditions that have begun to recover from the influence of the pandemic, so this is very supportive of quickly achieving their desire to marry. For couples who have previously been married and want to remarry, of course there are other requirements that must be met. Thus, sometimes some couples take shortcuts in falsifying their identity, such as being a widow or a virgin, in order to achieve their desire to get married officially. This is not impossible, in fact, it often happens that prospective female partners deliberately fake their identities to be accepted by male partners who are still virgins. The main problem in this research is how to implement the husband's right to annul the marriage due to falsifying the identity of the prospective wife, as well as how the judge's legal considerations are in resolving this problem. This study uses qualitative research methods with a normative descriptive approach. Data sources are based on literature studies and court decisions which are then analyzed using the content analysis method. The research results prove that the husband's rights in cases of identity fraud by his future wife are protected by the state based on statutory regulations so that the husband can take legal action to defend his rights. The judge in this case has given appropriate legal considerations so that no party is harmed as a consequence of their respective actions.